Analisis Pengaruh Indeks Zakat Nasional (IZN) terhadap Pengumpulan Zakat per Kapita di Indonesia - Zakirullah; Nashr Akbar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the impact of the National Zakat Index (IZN) and the Provincial Minimum Wage (UMP) on zakat collection per capita in Indonesia. Using panel data from 32 provinces in Indonesia for the period 2020 to 2023, this study applies panel data regression with the Fixed Effect Model (FEM) approach. The analysis results show that both variables, namely IZN and UMP, have a positive and significant effect on zakat collection per capita. An increase in IZN, which reflects the quality of zakat governance, can enhance public trust, thereby increasing the amount of zakat collected. Similarly, an increase in UMP, which reflects the improvement in the economic welfare of the community, also contributes to the increase in zakat per capita. The findings of this study provide important implications for the National Zakat Agency (BAZNAS) and other zakat management organizations to continuously improve the quality of zakat management and encourage policies that can improve the welfare of the community through an increase in UMP.